Sistematika Ilmu Komunikasi - Efendi, Erwan; Novita, Dina; Erlangga, Kevin; Arsalan, Rizki; M Syuza, Ghazy; Syifa, Aisyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to evaluate the role that instructional communication plays in the learning process. This study use explanatory research methodologies in conjunction with a quantitative methodology. The study's findings demonstrate the significance of communication as a fundamental human need and as a means of communicating with others in order to exchange experiences, opinions, feelings, knowledge, and guidance. In order to transmit educational messages during the learning process, effective communication is also a crucial component of educational communication. Effective educational communication is defined as one in which the material presented by teachers is well-received, easily comprehended, and results in favorable student feedback. This research concludes that educators must acquire